Bentham and the common law tradition - Postema, Gerald J. (Oxford : Oxford University Press, 2019)
This text offers a philosophical interpretation of the historical debate between Bentham and classical Common Law theory, a debate that is fundamental to philosophical thought and has shaped contemporary conceptions of nature, tasks and limits of law and adjudication. The author draws on the full range of Bentham's published and unpublished writings, and explores the philosophical foundations of Common Law theory, focusing particularly on the writings of Sir Matthew Hale and David Hume.
This edition also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 30, 2019).
Keywords: Common law; Bentham, Jeremy, -- 1748-1832.